Transformational infrastructure for development of a wellbeing economy in Africa - Mebratu, Desta; Swilling, Mark (STIAS series., 2019)
"African countries face unprecedented challenges of defining a future development pathway in a resource- and carbon-constrained world. This book addresses this challenge, with special reference to the set of infrastructure that most African countries require to meet the sustainable development goals and fulfil the aspirations of Agenda 2063. Infrastructure is a key factor that determines how resource and energy flow and transform through socio-economic systems. Decisions made today by African countries on their infrastructural configuration will determine the inclusivity, resource intensity and climate resilience of their development pathways for decades to come. This book is a product of a two⁰́₁year research conducted by a group of African scholars who have an extensive academic and practical experience on the development of key infrastructure sectors in Africa."--Publisher's description.